"DIE FRANSE KOLONEL" – VEGGENERAAL GRAAF GEORGES HENRI ANNE – MARIE VICTOR DE VILLEBOIS MAREUIL (1847-1900) - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
"Ardent passions, high hopes and powerful convictions are all necessary to make human minds move". Alexis de Tocqueville (1858) "Without this passion, and without the courage of his convictions, col Count de Villebois Mareuil would not have come to this country, without them, he would not have fought for the cause of the Boer republics and he would not have laid down his life for the ideals he believed in". Vice-Admiral H.H. Bierman, SSA, OBE, Commandant-General, SADF, Magersfontein, 14.8.1971